Peran Ikatan Pelajar dan Mahasiswa Sirenja dalam Memajukan Pendidikan di Kecamatan Sirenja Kabupaten Donggala - H. Pelu, Rehstaat; Kapile, Charles (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2022)
The purpose of this study was to determine the role of the Sirenja Student and Student Association in advancing education, the contribution of the Student and Student Association and the obstacles in advancing education in Sirenja District, Donggala Regency. This study uses descriptive qualitative research methods, data collection techniques used are library research and field research consisting of observation, interviews and documentation. This study uses an interactive model of data analysis technique, which has three steps, namely: data reduction, data display, and conclusion drawing. The results of this study indicate that the role of the Sirenja Student and Student Association in advancing education in Sirenja District from 2018 to 2020 is able to encourage and motivate Sirenja children to continue their education to a higher level. Contribution of the Sirenja Student and Student Association in advancing education in Sirenja District by encouraging associations that lead to education for Sirenja students and students in Palu City. The Sirenja Student and Student Association faces obstacles in advancing education in Sirenja District, by coordinating and providing input to the District and Village governments, to pay more attention to education.